Environmentally Smart House Services for the Children in The City of Bekasi, Indonesia - Hermawan, Rivaldo; Situmorang, Rahel; Muhamad Taki, Herika (Journal of Community Based Environmental Engineering and Management, 2024)
The city of Bekasi was awarded as one of child-friendly cities in Indonesia, by the Ministry of Women’s Empowerment and Child Protection in 2022. The city government is committed to fulfilling children’s rights, included in a Bekasi City Regional Regulation Number 13 of 2017, concerning child friendly cities. To fulfill children’s rights, the Bekasi City government built smart homes to improve child-friendly cities. Smart homes are a facility used for the children, which they use to learn, play and create things, without any charge. Currently, there are 7 smart houses built in Bekasi City, with another 5 being planned to be built in every sub district. The aim of this research was to identify the service coverage of 7 smart houses that serve Bekasi City, and to provide some recommendations for those to be built. This research used a mixed method, which involved an observation assessment, a score analysis and a spatial analysis. The results of the study showed that, of the 7 smart houses in Bekasi City located in several subdistricts, two were in good conditions (Pondok Gede and Bekasi Timur), three were in moderate conditions (Bekasi Selatan, Mustika Jaya, Rawa Lumbu), and the remaining two were in bad conditions (Medan Satria, Bekasi Utara). It can also be concluded that, based on the service coverage, the Pondok Gede covered another 5 districts, with a distance of 3100 m.